Edukasi Cuci Tangan Pakai Sabun Sebagai Upaya Peningkatan Kualitas Kesehatan di Lingkungan SD Negeri Ai Limung - Ana Lestari; Luh Putu Sri Yuliastuti; Iga Maliga; Rafiah Rafiah; Asri Reni Handayani; Herni Hasifah; Nur Arifatus Sholihah (Universitas Kristen Indonesia Toraja, 2024)
School-aged children have a habit of paying less attention to hand washing behavior, especially in the school environment. Although simple and effective, promoting hand washing for disease prevention is still a challenge. The habit of washing hands with soap is still a global concern because people still forget the habit of washing their hands. The focus of the activity is school-aged children who will become